(untitled) (REMUNOM, 2025)
This study aims to investigate the effects of dance practice on mental health, with an emphasis on reducing stress and anxiety levels. Through a literature review, scientific studies and academic publications were analyzed, exploring dance as an integrative and therapeutic bodily practice. The research shows that, in addition to physical benefits, dance promotes emotional balance, social interaction, and mood regulation, contributing to psychological well-being. The analyzed data suggest that incorporating dance as a complementary resource to conventional approaches in mental health care can be effective in promoting quality of life and preventing psychological disorders. It is concluded that valuing expressive and integrative practices in the health field represents a relevant strategy for the development of public policies aimed at comprehensive individual care.